Structural, Optical and Morphological Characterization of Cdse/Cds Core / Shell Quantum Dots Synthesized via Chemical Bath - Al-Beayaty, Mohammed Ali H; abbas, Lamiaa kh; mohammed, Rana kadhim (Iraqi Journal of Science, 2021)
CdSe/CdS Core/shell nanostructures were prepared through the chemical synthesis method. XRD ,FESEM and TEM investigations confirmed the formation of core/shell structure for the sample. The AFM measurement was employed to reveal the morphology of the prepared thin films. Optical characterizations of the quantum dots were done by UV-visible and photoluminescence spectra. It was found that the quantum dots prepared has good optical properties. Due to the presence of shell coating on core CdSe, the energy gap of the core/shell nanomaterial were increased from 2.2 to 2.3eV. The resulted QDs are a promising candidate for photovoltaic and biosensor applications.